HUBUNGAN PEMBERIAN ASI EKSLUSIF DAN STATUS GIZI TERHADAP KEJADIAN DIARE PADA ANAK USIA 7-12 BULAN DI PUSKESMAS SOKOREJO KOTA PEKALONGAN - Raysha Riezky Filasani Darmawan; Esti Widiasih; Nanik Marfu’ati (Jurnal Kesehatan, 2025)
Background : Diarrhea is included in category of diseases that have possibility to be an extraordinary incident and become as endemic disease so that it can cause a high deaths numbers. Based on data in 2019, the number of children under five years old with diarrhea was 5,294 cases with diarrhea case discovery at Puskesmas Sokorejo reaching 310 cases. There are several risk factors for diarrhea including exclusive breastfeeding and nutritional status. Purpose : The aim of this research was to find out the relationship between exclusive breastfeeding and nutritional status with the incidence of diarrhea in children aged 7-12 months at Puskesmas Sokorejo Pekalongan City. Methods : This is analytic observational study with a case control. The sample consisted of 64 children through Consecutive Sampling technique. The research are used anthopometric data, medical record of breastfeeding and history of diarrhea. Data were analyzed using Chi Square technique with Odds Ratio. Results : Bivariate analysis showed that exclusive breastfeeding was significantly related to incidence of diarrhea in children 7-12 months (p=0.003; OR=7.72), means that children who weren’t given exclusive breastfeeding had 7.72 times higher risk of having diarrhea. Nutritional status was significantly related to incidence of diarrhea in children 7-12 months (p=0.005; OR=5.22), means that children with poor nutritional status had 5.22 times higher risk of having diarrhea. Conclusion : There’s a significant relationship between exclusive breastfeeding and nutritional status in children aged 7-12 months at Puskesmas Sokorejo Pekalongan City.